Analysis of Laparoscopic Ultrathin Choledochoscope Curative Effect on Common Bile Duct Exploration and Choledocholithotomy in 47 Cases - Liu, Yang; Yang, Tao; Liu, Jia-Hong; Meng, Xuan; Xia, Hong-Tian (Frontiers in Surgery, 2022)
Objective: The aim of the present study is to summarize the experience of using a 2.7 mm choledochoscope for laparoscopic cholecystectomy combined with an ultrathin choledochoscope for common bile duct exploration and choledocholithotomy in the treatment of cholecystolithiasis associated with choledocholithiasis after the implementation of strict inclusion and exclusion criteria. Methods: A retrospective analysis of 47 patients with cholecystolithiasis complicated with choledocholithiasis who were treated in the hepatopancreatobiliary surgery department of the Chinese People’s Liberated Army General Hospital between January 2015 and December 2019 was performed in the present study. Clinical data of laparoscopic cholecystectomy combined with ultrathin choledochoscope transcystic duct exploration for common bile duct and choledocholithotomy. Results: All 47 patients completed the operation successfully. The gallbladder duct was closed using a surgical clamp. Only 2 patients were administered with an abdominal drainage tube. The operation time was 50–160 min, the intraoperative blood loss was 5–50 ml, and the postoperative hospital stay was 2–8 days. No patients had serious complications, such as bile leakage, postoperative bleeding, cholangitis, biliary pancreatitis, and wound infection. Minor complications, such as abdominal pain (Abdominal pain was defined as a patient felt tolerable or unbearable abdominal pain but improved or disappeared with medication) and diarrhea, were present in a few patients; these improved after conservative treatment. There was no recurrence of calculi during the 1–5 years of follow-up, and the patient quality of life was good. Conclusion: Laparoscopic cholecystectomy combined with ultrathin choledochoscope common bile duct exploration and choledocholithotomy is a safe and effective method after adopting strict inclusion and exclusion criteria. This technology was started in the First Medical Center, Chinese People’s Liberation Army General Hospital in September 2009, and it has become extremely mature in the past five years.